The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/02626667.2019.1659509
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from checking the quality of openly accessible river flow data worldwide

Abstract: Advances in open data science serve large-scale model developments and, subsequently, hydroclimate services. Local river flow observations are key in hydrology but data sharing remains limited due to unclear quality, or to political, economic or infrastructure reasons. This paper provides methods for quality checking openly accessible river-flow time series. Availability, outliers, homogeneity and trends were assessed in 21 586 time series from 13 data providers worldwide. We found a decrease in data availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…Despite the large sample of river gauges, however, we experienced that it was not distributed well enough to cover the large domain. Screening of the gauged data quality showed that most regions worldwide have access to some highquality time series of river flow (Crochemore et al, 2019), but for the stepwise procedure applied here this was still not enough for many of the pre-defined calibration steps. Even when merging the original ESA land-cover classes before calibration (Table 4) sufficient gauged data were missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the large sample of river gauges, however, we experienced that it was not distributed well enough to cover the large domain. Screening of the gauged data quality showed that most regions worldwide have access to some highquality time series of river flow (Crochemore et al, 2019), but for the stepwise procedure applied here this was still not enough for many of the pre-defined calibration steps. Even when merging the original ESA land-cover classes before calibration (Table 4) sufficient gauged data were missing.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, time series could be downloaded for 11 369, while 10 336 could only assist with metadata, such as upstream area, river name, elevation, or natural or regulated flow. The time series were screened for missing values, inconsistency, skewness, trends, inhomogeneity, and outliers (Crochemore et al, 2019). Stations representing the resolution of the model (≥ 1000 km 2 ) and with records of at least 10 consecutive years between 1981 and 2012 were considered for model evaluation.…”
Section: Observed River Flowmentioning
confidence: 99%
“…In such scales, model calibration and verification procedures are usually straightforward and provide adequate performance for modeling purposes. Moreover, the information provided to users needs to (at least) be reliable and precise (Swart et al, 2017), which is a challenge for continental and global services, since their setup is strongly dependent on uncertain open global data sets (Crochemore et al, 2019;Kauffeldt et al, 2013) and hydrological models that can only represent limited but dominant processes (Archfield et al, 2015;Bierkens, 2015;Sood & Smakhtin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ground measurement datasets are laden by inconsistencies between measuring stations, for instance offering different time periods, measuring frequencies, and technical qualities (W. A. Dorigo et al, ; Hannah et al, ; Harris et al, ; United Nations Environment Programme, ). Crochemore et al () provides a methodological framework for quality checking large‐sample river flow datasets.…”
Section: Dataset Usability Challenges For Comparative Studiesmentioning
confidence: 99%